'Tech firms must act' after Taliban seize Afghans' biometric data. (September 2021) - Unknown
Abstract : Campaigners fear Taliban will use biometrics to track down Afghan citizens Tech firms must 'delete data and declare moratorium' in Afghanistan Governments and aid agencies should realise 'danger' of using biometrics Biometric tech firms are being urged to act over fears that the Taliban forces now ruling Afghanistan could exploit masses of Afghan citizens' biometric data to identify and target people who opposed them.